KEPUASAN KERJA GURU DITINJAU DARI PERAN SUPERVISI KEPALA SEKOLAH DASAR NEGERI DI KECAMATAN BOGOR UTARA - Yudhie Suchyadi; Nita Karmila; Nurlinda Safitri (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2019)
WORK SATISFACTION TEACHERS ARE REVIEWED FROM THE ROLE OF HEADMASTER SUPERVISION OF PRIMARY SCHOOL IN NORTH BOGOR DISTRICT This research is aims to examine teacher job satisfaction and variables that have a relationship with teacher job satisfaction, in this case the supervision of school principals and efforts to improve teacher job satisfaction. The method used in this study is a survey method with a correlational approach. The research variable consisted of an independent variable namely the supervision of the principal with the dependent variable namely teacher job satisfaction. This research was conducted at the Public Elementary School in North Bogor Regency, Bogor City. Research data collection is carried out by distributing questionnaires to respondents who have been selected as samples. The results of the questionnaire were collected and recorded to analyze data to test the research hypotheses and to find out the strength of the relationship between principal supervision and teacher job satisfaction. To test the research hypothesis and to determine the strength of the relationship between principal supervision and teacher job satisfaction, data analysis was performed using statistical tests in the form of correlations and simple linear regression, as well as multiple correlation and regression. Hypothesis testing is performed at the significance level a = 0.05. This study presents three main conclusions: There is a positive relationship between principal supervision and teacher job satisfaction, meaning that the higher the supervision of the principal, the higher the teacher job satisfaction shown by the regression equation Ŷ = 63.64 + 0.53X and the correlation coefficient ry = 0.520. Based on the findings, teacher job satisfaction can be increased through supervision of the school principal.